The flora of Newfoundland, Labrador, and St. Pierre et Miquelon - Waghorne, Arthur C. (Arthur Charles), 1851-1900.; Nova Scotian Institute of Science. (St. John's, N.F. : [s.n., 1898)
Offprint: Transactions of the Nova Scotian Institute of Science. Pt. 1 from: ser. 2, v. 1; pt. 2 from: v. 9, session 1894-95; pt. 3 from: v. 9, Dec. 1898. No more published. Title from cover. Mode of access: Internet.